2007
DOI: 10.1007/s00192-007-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training improves sexual function of women with stress urinary incontinence

Abstract: The aim of this study was to assess the effect of a program of supervised pelvic floor muscle training (PFMT) on sexual function, in a group of women with urodynamically diagnosed stress urinary incontinence (SUI), using a validated questionnaire. Incontinence episodes frequency and continence pads used per week were measured before and after treatment using a 7-day bladder diary. Improvements in sexual function were assessed using the Female Sexual Function Index (FSFI). Seventy women completed the 12-month p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 33 publications
6
68
0
8
Order By: Relevance
“…Moreover, regular exercise increases cardiovascular and muscular endurance, which in turn strengthens marriage relationship and makes the person less likely to suffer from fatigue. The study results of Zahariou et al are consistent with the present study (21).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, regular exercise increases cardiovascular and muscular endurance, which in turn strengthens marriage relationship and makes the person less likely to suffer from fatigue. The study results of Zahariou et al are consistent with the present study (21).…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, Baytur et al 9 did not find a correlation between PFM strength (using the perineometer) and sexual function (through the FSFI questionnaire) postpartum. However, a PFM training program with nonpregnant women found that those with weak PFMs and who received training had positive results in sexual function, also verified through the FSFI 35 . This demonstrates that stronger muscles are linked to better sexual function.…”
Section: Pfm Strength and Sexual Functionmentioning
confidence: 88%
“…Among these factors, pregnancy and childbirth are most closely related to female pelvic floor dysfunction. In the process of pregnancy and childbirth, chronic fetal oppression of the pelvic floor musculature and innervation of the supporting tissue of the pelvic cavity can injure the pelvic floor muscles and cause urethral sphincter denervation damage; the fetus passing through the soft birth canal can also directly damage the pelvic floor, anal sphincter, and perineum (Payne, 2008;Zahariou et al, 2008;Shek et al, 2012).…”
Section: Discussionmentioning
confidence: 99%